PENGARUH PENGGUNAAN SARI JAMBU BIJI TERHADAP KUALITAS ES KRIM - Indriany, Della Suci; Yulastri, Asmar; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was created by the utilization of guava processing that have not varies. This researceh was aimed to examine the benefits of giving guava fruit extract which includes 15%; 30% and 45% on the quality of the ice cream’s color, aroma, flavor, and texture. This research was a true experiment by involving completely randomized single-factor method, that was giving guava fruit extract at the rate of (0%; 15%; 30% and 45%) for three repititions. It used primary data from collecting the information from 30 panelists. Then, the data were presented in an ANOVA table, analysis of variance (ANOVA). If there was significant difference, it should be revealed by Duncan test. The result of the research showed that there were a siginifact influence between 0%; 15%; 30% and 45% for the ice crem quality on its pink color, the aroma and creamy texture although it still have a rich flavor with a sweet-tart taste. Based on data percentage analysis, to make guava ice cream with good color, good smell, and good quality is giving 45% guava extract. Thus, it is suggested to give 45% guava extract of the milk used to make good ice cream.Kata kunci: Guava Extract, Ice Cream, Quality